Histopathological study of toxicity mixture of cashew apple juice (Anacardium occidentale), cow milk and yogurt on the wistar rat - BOKOSSA YAOU, Innocent Padonou; AGBODJOGBE, Daniel; DJOGBE, Anayce A. Mikponsè; LOKO, CHRISTIAN FRÉDÉRIC SIMPLICE; DARBOUX, RAPHAËL BARTHÉLÉMY; LOZES, Evelyne; TCHEKESSI, C. K. Célestin; SACHI, Amour Pivot; BLEOUSSI, Roseline; MENSAH, Guy A. (My University, 2016)
The purpose of this study was to confirm or to deny the general opinion Benin people that the simultaneous consumption of dairy products, cow milk, yogurt (fermented cow's milk) with cashew apple juice is toxic to human and the animal. Histopathological examinations were performed on thirty Wistar rats consist of ten batches. Each batch is consisted of three rats. The first batch has served as a control and the remaining nine were treated differently. Cow milk, yogurt and cashew apple juice either alone or mixed with each others were administered to each rat at the rate of 2.0 ml / 200g of body weight. Histological observation of removed organs (stomach, liver and kidneys) within the treated batch showed that the organs of rats treated with cashew apple juice / cow milk /yogurt (respectively batch 2, 3, and 4) was not showing any structural abnormality. Similar types of findings were reported for the rat group treated with a mixture of juice and milk. However, it was reported that the juice-yogurt association has some action on the liver but it did affect the functioning or anatomy of other analyzed organs. It can be conclude that the juice and cow milk mixture are not toxic to animal cells, but the juice-yogurt mixture has some toxic effect on the liver cells only.
Keywords: Dairy products; Cashew apple juice; Toxicity; Histopathology; Wistar rats